B cell–intrinsic TBK1 is essential for germinal center formation during infection and vaccination in mice - Lee, MSJ; Inoue, T; Ise, W; Matsuo-Dapaah, J; Wing, JB; Temizoz, B; Kobiyama, K; Hayashi, T; Patil, A; Sakaguchi, S; Simon, AK; Bezbradica, JS; et al. (Rockefeller University Press, 2021)
The germinal center (GC) is a site where somatic hypermutation and clonal selection are coupled for antibody affinity maturation against infections. However, how GCs are formed and regulated is incompletely understood. Here, we identified an unexpected role of Tank-binding kinase-1 (TBK1) as a crucial B cell–intrinsic factor for GC formation. Using immunization and malaria infection models, we show that TBK1-deficient B cells failed to form GC despite normal Tfh cell differentiation, although some malaria-infected B cell–specific TBK1-deficient mice could survive by GC-independent mechanisms. Mechanistically, TBK1 phosphorylation elevates in B cells during GC differentiation and regulates the balance of IRF4/BCL6 expression by limiting CD40 and BCR activation through noncanonical NF-κB and AKTT308 signaling. In the absence of TBK1, CD40 and BCR signaling synergistically enhanced IRF4 expression in Pre-GC, leading to BCL6 suppression, and therefore failed to form GCs. As a result, memory B cells generated from TBK1-deficient B cells fail to confer sterile immunity upon reinfection, suggesting that TBK1 determines B cell fate to promote long-lasting humoral immunity.